Young mentors' relationship capacity: Parent–child connectedness, attitudes toward mentees, empathy, and perceived match quality. (February 2019) - Doty, Jennifer L.; Weiler, Lindsey M.; Mehus, Christopher J.; McMorris, Barbara J.
Because the responsibility of developing strong connections to mentees often depends on mentors themselves, examining mentor qualities and relational capacity may identify malleable factors—or potential points of intervention—to improve perceived match quality. Relational capacity has been proposed as a theoretical concept for understanding how mentors' previous experience, characteristics, and skills relate to mentoring quality. Our conceptual model posited that parent–child relationships build young mentors' relational capacity for successful mentoring relationships. Using data from young mentors age 15–26 participating in the Big Brothers/Big Sisters school-based mentoring program ( n = 155), this study extends current knowledge by examining potential mediators of the relationship between young mentors' perceived parent–child connectedness and perceived match quality. Attitudes toward mentees and empathy skills mediated the relationship between parent–child connectedness and perceived match quality. Findings suggest that parent–child connectedness contributes to attitudes and skills that may strengthen perceived match quality. From a positive youth development perspective, young mentors with low relational capacity may require support to ensure high-quality matches.